Active seeking of post‐donation information to minimize a potential threat to transfusion safety: A pilot programme in the context of the COVID‐19 pandemic. Issue 4 (23rd November 2021) - Lewin, Antoine; Renaud, Christian; Boivin, Amélie; Germain, Marc
Abstract: Background and Objectives: Early in the pandemic, the transmissibility of coronavirus disease‐19 (COVID‐19) by transfusion was unknown. We piloted a systematic, post‐donation outreach programme to contact blood donors and inquired about symptoms post‐donation. Materials and Methods: Persons who donated on on May 1 and 2, 2020 were contacted 3 days post‐donation, by phone to assess COVID‐19‐related symptoms. Half of the donors were administered a short questionnaire, consisting of only three questions. Others were questioned using a longer, more specific questionnaire. If symptoms were reported, products were quarantined until donors were contacted again by a trained nurse who more thoroughly assessed the likelihood of COVID‐19. Blood products were withdrawn if symptoms indicative of COVID‐19 were identified. Results: Of 654 donors, 609 (93.1%) were successfully contacted. Of 310 donors who answered the short questionnaire and 299 who answered the long questionnaire, 19 (6.1%) and 8 (2.7%) had one or more symptoms, respectively. Based on the nurses' assessment, two donations (0.3%) had to be withdrawn. Conclusion: These results suggest that actively seeking post‐donation information might be feasible to mitigate emerging, unqualified transfusion risks.